Anaphora and Cataphore Analysis in the Indonesian Film Dialogue "Dia Angkasa" Pragmatic Study - Siti Musdalifah Abd. Gani; Yunidar; Arum Pujining Tyas Tyas; Syamsudin; Ulinsa (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to analyze and describe the form and function of anaphora and cataphore in the dialogue of the film "Dia Angkasa", a pragmatic study. Despite its popularity, this film is still a topic that is not explored as an object that has not been studied academically, especially in pragmatic studies, and the combination of concepts between anaphora and cataphore with a pragmatic approach in one study is a potential for new research. The method used is qualitative with a descriptive approach, with data collection through listening, recording, and dialogue documentation techniques in the film. The data analysis technique in this study uses techniques from the Miles and Huberman approach, namely data reduction, data presentation, and conclusion drawn.  The results of the research data findings show that this film uses twelve anaphora references which are divided into six persona pronouns, and six demonstrative pronouns. Meanwhile, the cataphore reference has seven data divided into six persona pronouns, and one demonstrative pronoun. These two references have a function to avoid repeating the same words so as to create language efficiency, maintain the continuity of the storyline, and in each form the pronoun has a different function, where the persona pronoun refers to one or more people in the scope of the conversation, while the demonstrative pronoun becomes a tool to point to something that has already been mentioned or that will just be mentioned. Thus, this study illustrates those pragmatic elements, especially anaphora and cataphores, play a major role in creating deep meaning, as well as maintaining the continuity of the story, and making language efficient.